Statistical Models for Vaginal Microflora: Identifying Women at Risk for Group B Streptococcus Colonization as a Test of Concept. Issue 5 (1997) - Lee, Mei-Ling T.; Ross, Robin A.; Onderdonk, Andrew B.
Abstract : Objective: The purpose of this study was to formulate a statistical model that relates human microflora to probabilities for vaginal colonization by group B Streptococcus (GBS). Methods: Longitudinal observations of total bacterial concentrations at various times during the menstrual cycle were obtained from overtly healthy, non-pregnant, menarcheal women. During each menstrual period and at appropriate intermenstrual times, the duplicate swab technique was used to sample the vaginal vault to obtain microbiologic samples. Women were identified as being colonized with GBS if their samples contained faculative gram-positive cocci. The method of generalized estimating equation (GEE) was used to model the longitudinal data set. Results: Concentrations of Corynebacterium sp., Streptococcus spp., and total anaerobic bacteria were found to be risk factors for GBS colonization. The sensitivity of the predictive model is 84% and the specificity is 79%. Conclusions: Although vaginal cultures for GBS are routinely performed to detect colonization, the statistical model described identifies associated risk factors which may be important determinants for GBS colonization.